ANALISIS STATIK BEBAN GEMPA PADA PERENCANAAN STRUKTUR GEDUNG REKTORAT UNHASY TEBUIRENG JOMBANG - Titin Sundari; Abdiyah Amudi; Totok Yulianto; Rahma Ramadhani (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
Static analysis is a simplification of dynamic analysis. Earthquake vibrations cause lateral forces at the base of the structure, and will be distributed on each floor of the building as lateral level forces. This analysis is suitable for regular building shapes. In accordance with SNI 1726: 2012, the value of the base shear force V is 103,039 kg for the X and Y directions. The displacement value is 54 mm and drift ratio ∆ < ∆a (allowable)